Pengaruh Bimbingan Belajar Terhadap Perkembangan Membaca Siswa Kelas 1 SDI Bandar Kidul Kota Kediri - Nirra Fatmah; Evi Ningtyas (Jurnal Pendidikan Educandum, 2026)
This study is motivated by the low reading ability of elementary school students, which has an impact on their difficulties in understanding learning materials and on the development of early literacy skills. Among 20 first-grade students at SDI Bandar Kidul, Kediri City, 10 students are not yet fluent in reading, 7 students experience difficulties in reading, and 3 students are unable to read at all. This condition highlights the need for learning guidance (tutoring) as one of the possible solutions. The research problems addressed in this study are how learning guidance influences the reading development of first-grade students at SDI Bandar Kidul, Kediri City, and to what extent this influence contributes to improving students’ reading abilities. Accordingly, this study aims to examine the effect of learning guidance on the reading development of first-grade students at SDI Bandar Kidul, Kediri City, and to measure the extent of its contribution in helping students improve letter recognition, syllable decoding, reading words and simple sentences, as well as enhancing students’ self-confidence.